Kualitas fisik susu goreng dengan waktu penyimpanan dingin yang berbeda - Haris Wahyudi; Metha Monica; Fatati Fatati (CV. SINAR HOWUHOWU, 2026)
This study aimed to analyze the effect of cold storage duration on the physical quality of fried milk, including pH, moisture content, and yield. A Completely Randomized Design (CRD) was used with four storage treatments (0, 1, 2, and 3 hours) at 4°C and five replications. The results showed that increasing storage time significantly decreased pH and moisture content. The pH value declined from 7.29 at 0 hours to 7.23 at 3 hours, indicating increased acidity. Moisture content decreased from 29.8% to 24% due to water evaporation during cold storage. The highest yield was obtained at 2 hours of storage (11.02%) and slightly decreased at 3 hours. It can be concluded that storage for 2 hours at 4°C was the optimal treatment for maintaining the physical quality of fried milk while ensuring product safety and shelf life.